2015
DOI: 10.3748/wjg.v21.i31.9367
|View full text |Cite
|
Sign up to set email alerts
|

Fluid resuscitation in acute pancreatitis: Normal saline or lactated Ringer's solution?

Abstract: Our study failed to find any evidence that the administration of RL in the first days of AP leads to improved clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
0
22
0
3
Order By: Relevance
“…Most of these 19 studies were reports of a comparison between Ringer's lactate with normal saline in post‐ERCP pancreatitis. Finally, five studies including 428 participants met the eligibility criteria. Two of the included studies were retrospective observational cohort studies and three were RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these 19 studies were reports of a comparison between Ringer's lactate with normal saline in post‐ERCP pancreatitis. Finally, five studies including 428 participants met the eligibility criteria. Two of the included studies were retrospective observational cohort studies and three were RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…hydration in these patients . Recent studies have shown that use of a more balanced solution, Ringer's lactate, can improve mortality rates and decrease the development of SIRS over 24–48 h in these patients, compared with normal saline . However, existing data are conflicting and are limited to small‐sized studies.…”
Section: Introductionmentioning
confidence: 99%
“…Aggressive intravenous hydration with lactated Ringer's solution appears to reduce the development of post-ERCP pancreatitis and is not associated with volume overload 72 . Other studies show no added benefit from lactated Ringer's solution compared to normal saline in terms of mortality and the duration of hospital stay 73 .…”
Section: (Grade 2/b Full Agreement)mentioning
confidence: 95%
“…Guidelines on acute pancreatitis advocate the use of lactated Ringer's solution based on one well‐designed study that was terminated after an interim analysis of 40 patients . This is at odds with a recent retrospective study that did not find a significant difference between lactated Ringer's solution and normal saline in terms of disease severity, pancreatic necrosis and mortality . The included studies offer no clear guidance on this issue.…”
Section: Discussionmentioning
confidence: 99%